Uruguay y los procesos de integración regional: trayectoria, cambios y debates = Uruguay and regional integration processes: paths, changes, and debates - Revelez, Lincoln Bizzozero (Civitas - Revista de Ciências Sociais, 2010)
This article analyzes Uruguay’s evolution in the Latin-American regional integration process. In order to do that it shows right from the start some conceptual explanations on different moments of the regional integration process and on the new regionalism conditions and principles of this country external policies. Based on the argument that new regionalisms and especially all strategic new regionalisms from the 21st century rethink the basis of each country’s external policies, among them Uruguay. In Uruguay’s case it means rethinking the principles of regional equidistance with its neighbors. Such a fact necessarily makes Uruguay think over its role in the new regional construction against the resources that it gets from the integration process